2019
DOI: 10.1016/j.actbio.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The multiscale structural and mechanical effects of mouse supraspinatus muscle unloading on the mature enthesis

Abstract: The musculoskeletal system is sensitive to its loading environment; this is of particular concern under conditions such as disuse, paralysis, and extended-duration space flight. Although structural and mechanical changes to tendon and bone following paralysis and disuse are well understood, there is a pressing need to understand how this unloading affects the bone-tendon interface (enthesis); the location most prone to tears and injury. We therefore elucidated these effects of unloading in the entheses of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 71 publications
5
75
1
Order By: Relevance
“…Reduced loading could result in significant structural consequences at several hierarchical scales, with an increased risk of mechanical failure, as demonstrated in mouse models. 64 Finally, in keeping with this finding, some reports showed that many patients with axSpA reported injuries or trauma as a potential trigger for their disease onset. 62 65 …”
Section: The Role Of Physical Exercise In Axspa: To Move or Not To Momentioning
confidence: 53%
“…Reduced loading could result in significant structural consequences at several hierarchical scales, with an increased risk of mechanical failure, as demonstrated in mouse models. 64 Finally, in keeping with this finding, some reports showed that many patients with axSpA reported injuries or trauma as a potential trigger for their disease onset. 62 65 …”
Section: The Role Of Physical Exercise In Axspa: To Move or Not To Momentioning
confidence: 53%
“…This pattern, which involved smaller muscle volume in the stimulated limbs, is a normal adaptation to reduce muscle fatigue by increasing the relative abundance of narrower fiber types 27 (also see below). The results of a recent experimental study on adult mice established a direct association between unloading and bone loss at entheseal areas 26 . On this basis, the observed entheseal differences between stimulated and unstimulated limbs may be due to a combination of increased and decreased muscle use, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…18 ). Moreover, recent experimental research on adult mice entheses 26 found that artificial muscle paralysis for 21 days led to significant bone loss in entheseal areas at the millimeter scale.…”
Section: Introductionmentioning
confidence: 99%
“…The IKKβ inhibitor was administered orally, leading to a systemic effect, including to the humeral head bone adjacent to the healing interface. Because mineral content correlates with tendon enthesis mechanical properties 12 and loss of mineralized tissue at the attachment site correlates with higher rates of retearing after surgical repair, 15 we examined bone morphometry of the humeral head. While IKKβ inhibitor treatment prevented some of the mineral and trabeculae losses that are commonly seen after rotator cuff repair, systemic inhibition of IKKβ also led to decreases in overall humeral head BV/TV and cortical thickness at an earlier timepoint.…”
Section: Discussionmentioning
confidence: 99%